A visual analysis of packaging and labeling design of traditional snack foods in context of Malay SME in Malacca / Azahar Harun, Ariff Ali and Ida Hartini Zainol (Institute of Research, Development and Commercialization (IRDC), 2004)
The purpose of this research is to analyze the packaging and labeling design of the traditional snack foods produced by the Malay SME in Malacca. Traditional snack foods are a type of meal, which is popular among Malaysian consumer especially during festive seasons. However, in spite of its reputation, it is found that some of the products are still packed in cheap packaging material hence lacked the sense of value and quality. As a result, many snack food producers have difficulty in terms of positioning their products in major wholesale outlets or exporting to overseas market. Part of the reason is because the packaging and labeling method fail to comply with certain standard set by the government. In this paper, there are three interrelated phases of study. The first phase was a one-to-one interview with several respondents, which include a CEO of the Production Technology Division of the Chief Minister Department of Malacca, a Senior Executive Designer of Sirim Berhad, a Graphic Design practitioner and a number of Malay SME entrepreneurs in Malacca. In the second phase, the researcher conducted a visual analysis by visiting several places including manufacturing premises, food expositions, and retail outlets. Through this process, the researcher observed and analyzed the packaging and labeling of the traditional snack foods in the aspect of visibility, information, emotional appeal and workability. Finally, in the last phase of the study, the researcher conducted a survey of consumer preferences. 200 respondents were selected among the visitors of the "Asean Halal Food Exhibition" which was held at the MITC in September 2004. The respondents were asked to complete a questionnaire concerning their preferences on packaging and labeling of the traditional snack food of Malacca. Their responses were documented and presented in descriptive essay format.